2018
DOI: 10.7575/aiac.ijels.v.6n.1p.27
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes of Secondary School Students Toward School And Reading: A Comparison In Terms of Mother Tongue, Gender And Class Level

Abstract: It is important to determine whether the school attitude of secondary school students has an influence on the reading attitude. For this purpose, such a study was conducted at secondary school level. In addition, the extent to which such variables as mother tongue are determinative in this context has been examined.The objective of this study is to examine the relationship between the attitudes of 5 th , 6 th , 7th and 8 th grade secondary school students toward the school and reading. In addition, the study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The programs could have affected the lower level of attitudes of the 11 th graders. Yıldız and Kızıltaş (2018) revealed that the native language was related to the attitudes. Schools are expected to contribute to the enjoyment of the native language and preservation, development, and dissemination of language.…”
Section: Results a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The programs could have affected the lower level of attitudes of the 11 th graders. Yıldız and Kızıltaş (2018) revealed that the native language was related to the attitudes. Schools are expected to contribute to the enjoyment of the native language and preservation, development, and dissemination of language.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…On the other hand, there are studies showing people's positive attitudes both toward their native language and certain nonnative local languages (Yıldız and Kızıltaş, 2018;Zungu and Pillay, 2010). For example, Yalınkılıç and Yağmur (2014) found that bilingual Western Thrace Turks had positive attitudes toward the Turkish language and pointed to the use of the language in daily life as means to maintain their identities.…”
Section: Results a N D Discussionmentioning
confidence: 99%